Effects of lightning electromagnetic field due to lightning strikes on a tall structure / Norhidayu Rameli ... [et al.] - Rameli, Norhidayu; Abd Kadi, Mohd Zainal Abidin; Izadi, Mahdi; Azis, Norhafiz (UiTM Press, 2023)
It is a fact that tall towers have a high chance of being struck by lightning, resulting in an induced voltage on a piece of a conductor through the coupling effect of the electromagnetic field. As a result, it disrupts the power supply on the distribution power line. This paper proposes new expressions of the lightning electromagnetic field (LEMF) and further investigates their effects due to lightning strikes on a tall structure. The new expression is calculated using trapezoidal and finite-difference time-domain (FDTD) methods and programmed through MATLAB. The expression was verified by literature measurement work and obtained with a reasonably accurate match. Also, the effects of LEMF due to the lightning current front time and the ground impedance were investigated. The result indicated that at least 50% of the LEMF peaks experience a reduction as the current front time increases and declines as the ground impedance increases. Hence, these results significantly impact the assessment of lightning-induced voltages in the distribution power line. It may help determine an appropriate solution for lightning protection, including selecting a line arrester rating, improving the basic insulation level (BIL) and the ground system.